The decreasing British influence on Cyprus 1955-1974 - Kacziba, Péter (Études sur la Région Méditerranéenne, 2012)
Once the Mediterranean Sea was the "lake" of the British Empire. Their ships were patrolling the most important sea straits, meanwhile the British Colonies were controlling the most important trading routes of the sea. The British Empire was the most significant great power in the region for centuries, however, British influence suffered important losses in the World War I. Nevertheless, London was able to keep her positions until the Second World War, but after that London lost - as a result of financial crisis - her strength to keep the Empire in one block. The decreasing British influence on Cyprus was already noticeable after the World War II, however, it only became unquestionable in the mid- 1950s. The decreasing British influence on Cyprus in the period of 1955-1974 could be divided into three main stages: (2.) the period of 1955-1960, when London still attempted to keep her colonial leadership over Cyprus but already realized the possibilities and acted to solve the problem; (3.) the period of 1960-1964 when Great Britain was still a significant regional power in Cyprus but by the end of the era London had to realize her loss of power; (4.) and the period of 1964-1974, when the British were intentionally reducing their influence on Cyprus to keep their positions and obtain a neutral standing on the Cyprus Question.